PENERAPAN PERDA NO. 1 TAHUN 2015 TENTANG BANGUNAN GEDUNG DI KOTA BUKITTINGGI - Gita Triana; Afriva Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aimed to determine the implementation of the regional government No. 1 of 2015 concerning building in Bukittinggi City.The background of this research is because there are still buildings that were built without IMB, the community still builds buildings in areas that are not in accordance with the land designation, low willingness of the community to comply with regulations and there are buildings that have permits, but the construction process is not appropriate with permission that has been issued. This research is a qualitative research using descriptive method. Data collection techniques use interview techniques, field observations, and documentation studies. The informants in this study were determined through purposive techniques. Data analysis techniques can be carried out namely data collection, data reduction, data presentation, and then draw conclusions. The results showed that the implementation of the Bukittinggi City regional government policy on building permits had not yet proceeded, such as people building buildings without permits, buildings that have permits but when the construction process is carried out is not in accordance with the provisions of permits that have been issued, the lack of supervision carried out by the local apparatus organization is related. constraints faced in implementing this policy such as communication constraints in the form of uneven socialization, the resources owned by the related local apparatus organization are inadequate and the lack of willingness of the community to comply with regulations.